Phytohormone-Based Biostimulants as an Alternative Mitigating Strategy for Horticultural Plants Grown Under Adverse Multi-Stress Conditions: Common South African Stress Factors - Zenzile Khetsha; Elmarie Van der Watt; Maxson Masowa; Lesetja Legodi; Sanelisiwe Satshi; Lethabo Sadiki; Kenoni Moyo (Caraka Tani: Journal of Sustainable Agriculture, 2024)
Worldwide, it has been recorded extensively that plants are subjected to severe abiotic and biotic stressors. The scientific research community has widely reported that multi-abiotic stressors cause horticultural crop losses, accounting for at least 50 to 70% of the crop yield and quality losses. Therefore, this review focused on the detrimental effects caused by abiotic stress factors occurring in single-, combined- and multi-cell stresses on horticultural plants worldwide, along with the best production systems practices for mitigation during and post-single and combined abiotic or multi-stress damages. A conclusion and recommendation could be reached using the pool of research material, which constituted research articles, reviews, book chapters, thesis, research short communications and industrial short communications from at least twenty-five years ago. Findings showed that some of the leading abiotic stresses are single- and combined abiotic stressors like water deficit, salinity, soil pH, phosphate deficiency, wounding, soil density and pot size. Established commercial and smallholder farmers are globally adapting to plant growth regulators and biostimulants as part of their production systems. However, as much as the effectiveness of biostimulants containing humic acids, algal extracts, plant growth-promoting microorganisms and phytohormones has been reported to promote plant development under multi-stress, only a few studies are focusing on organic phytohormone-based biostimulants on horticultural crops grown under adverse multi stress factoring. In conclusion, the review recommends alternative solutions for emerging South African farmers and growers who cannot afford agricultural insurance options and energy alternatives on the common single- and combined abiotic- or multi-stress-factors.